Book Reviews (Res Medica, 2013)
TEXTBOOK OF MEDICAL TREATMENT. Edited by Sir Derrick: Dunlop, Sir Stanley Davidson, S. Alstead. Eighth edition. Edinburgh: E. & S. Livingstone1961. Pp. 983 and XIX. Price 60s.New editions of this textbook have been appearing regularly and frequently since its first publication just twenty two years ago. This is undoubted proof of its popularity and a reflection of the steady advances Medical Treatment has made over the years.